(untitled) (BIBECHANA, 2024)
Rational selection of active biomolecules in the synthesis of nanoparticles for reducing the precursor and functionalizing the nanoparticles (NPs) can offer remarkable comeback of biocompatibility and biological applicability. This work aimed at the synthesis of a cost-effective, ecofriendly, and a facile approach of silver nanoparticles (AgNPs) using methanolic leaf extract of Artemisia vulgaris. The phytochemical constituents present in the methanolic extract were characterized by qualitative chemical tests and spectroscopic measurements and employed for the reduction of silver nitrate into silver nanoparticles. Formation of AgNPs was monitored by UV-visible spectroscopic measurement. Fourier transform infrared (FTIR) spectroscopy reflected the presence of characteristic functional groups associated with the phytochemical constituents involved in the formation of nanoparticles. The crystalline phase and morphology of the NPs were assessed form X-ray diffraction (XRD) spectra and field emission scanning electron microscopy (FESEM), respectively. XRD pattern revealed the crystalline nature of nanoparticles with grain size of ∼ 28 nm based on the Debye Scherer formula. Study of antimicrobial activity of AgNPs against Gram-positive bacteria Bacillus subtili, Gram-negative bacteria Escherichia coli, and fungus Candida albicans exhibited good potential to control the bacterial and fungal growth.